Determinants affecting the preferences of selected Malaysian millennial towards international brands / Muhammad Abdullah Mortadza - Mortadza, Muhammad Abdullah (Faculty of Business Management, 2017)
This research paper explains the study of determinants affecting selected Malaysia millennial preferences towards international brands. The determinants that are brand innovation, brand trust and brand loyalty a well-documented in the literature. The study explains the millennial preferences towards international brands in the scope of gadgets such as smartphone, laptop and tablets where millennial have interest in this type of technology. A survey was conduct on a sample of 155 International Business degree students of UiTM Kampus Bandaraya Melaka. The findings show that the brand innovation and brand trust significantly influences millennial preferences towards international brands. Therefore the present study is to determine the relationship between independent variable that is brand innovation, brand trust, brand loyalty and dependent variable that is millennial preferences towards international brand. The data of the study were collected using questionnaire and by using SPPS software program. The findings shows that brand innovation and brand trust has a positive impact affecting millennial preferences towards international brands where else brand loyalty is not significant influence the dependent variable.